Impact of Remote Ischemic Postconditioning during Primary Percutaneous Coronary Intervention on Left Ventricular Remodeling after Anterior Wall ST-Segment Elevation Myocardial Infarction: A Single-Center Experience - Elbadawi, Ayman; Awad, Omar; Raymond, Ramy; Badran, Haytham; Mostafa, Ahmad E.; Saad, Marwan (International Journal of Angiology, 2017)
The role of remote ischemic postconditioning (RIPostC) in improving left ventricular (LV) remodeling after primary percutaneous coronary intervention (PCI) is not well established. To determine the efficacy and safety of RIPostC in improving LV remodeling and cardiovascular outcomes after primary PCI for anterior ST-elevation myocardial infarction (STEMI). Seventy-one patients with anterior STEMI were randomized to primary PCI with RIPostC protocol (n = 36) versus conventional primary PCI (n = 35). Primary outcomes included LV remodeling and LV ejection fraction (LVEF) at 6 month follow-up using transthoracic echocardiography. Secondary outcomes included infarct size, ST-segment resolution (STR) ≥70%, Thrombolysis in Myocardial Infarction (TIMI) flow grade, and myocardial blush grade (MBG). Major adverse cardiac events (MACEs) were also assessed at 6 months. Safety outcome included incidence of acute kidney injury (AKI) postprimary PCI. Sixty patients completed the study. At 6 months, there was no significant decrease in the incidence of LV remodeling with RIPostC group (p = 0.42). Similarly, RIPostC failed to show significant improvement in LVEF. However, STR ≥ 70% after primary PCI was achieved more in the RIPostC group (p = 0.04), with a trend toward less AKI in the RIPostC group (p = 0.08). All other secondary end points, including MACEs at 6 months, were similar in both groups. RIPostC might be associated with better STR after reperfusion as well as less incidence of AKI in patients undergoing primary PCI for anterior wall STEMI, indicating potential benefit in those patients. Whether this role can be translated to better outcomes after primary PCI warrants further investigation.
Keywords: coronary artery disease; acute anterior wall myocardial infarction; primary PCI; reperfusion Injury; remote ischemic postconditioning; remodeling